The use of metaphors by service users with diverse long-term conditions: a secondary qualitative data analysis - Heidi Lempp; Chris Tang; Emily Heavey; Katherine Bristowe; Helen Allan; Vanessa Lawrence; Beatriz Santana Suarez; Ruth Williams; Lisa Hinton; Karen Gillett; Anne Arber (Qualitative Research in Medicine & Healthcare, 2024)
Long-term conditions and accompanied co-morbidities now affect about a quarter of the UK population. Enabling patients and caregivers to communicate their experience of illness in their own words is vital to developing a shared understanding of the condition and its impact on patients’ and caregivers’ lives and in delivering person-centred care. Studies of patient language show how metaphors provide insight into the physical and emotional world of the patient, but such studies are often limited by their focus on a single illness. The authors of this study undertook a secondary qualitative data analysis of 25 interviews, comparing the metaphors used by patients and parents of patients with five longterm conditions. Analysis shows how similar metaphors can be used in empowering and disempowering ways as patients strive to accept illness in their daily lives and how metaphor use depends on the manifestation, diagnosis, and treatment of individual conditions. The study concludes with implications for how metaphorical expressions can be attended to by healthcare professionals as part of shared care planning.